1981
DOI: 10.1620/tjem.134.321
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of adult-type citrullinemia with administration of citrate.

Abstract: A 48-year-old man who showed a regular diurnal fluctuation of blood ammonia level was diagnosed as adult-type citrullinemia with quantitative estimation of plasma amino acids and urea cycle enzymes in the liver. The restriction of daily protein intake less than 50 g and oral administration of lactulose had no effect on the blood ammonia level. The efficacy of four amino acid solutions which had been used in order to improve the hepatic encephalopathy was compared each other in this case. Glutamate-arginine mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Asparagine may be substituted for them, although it should be noticed that asparagine loads additional nitrogen onto the urea cycle. Citrate has been used effectively in some cases for CTLN2 therapy (Yajima et al 1981). Citrate supplies oxaloacetate via ATP citrate lyase, although it may also supply acetyl-CoA for the synthesis of fatty acids, resulting in fatty liver and hyperlipidemia.…”
Section: Ctln2 and Niccd As A Citrin Deficiencymentioning
confidence: 99%
“…Asparagine may be substituted for them, although it should be noticed that asparagine loads additional nitrogen onto the urea cycle. Citrate has been used effectively in some cases for CTLN2 therapy (Yajima et al 1981). Citrate supplies oxaloacetate via ATP citrate lyase, although it may also supply acetyl-CoA for the synthesis of fatty acids, resulting in fatty liver and hyperlipidemia.…”
Section: Ctln2 and Niccd As A Citrin Deficiencymentioning
confidence: 99%
“…1(A)), despite both substances having been reported to be effective treatments in some CTLN2 cases [35,36]. Although Asp is known to be impermeable to the plasma membrane of periportal hepatocytes [37], a specific plasma membrane transporter can import citrate into the liver [38].…”
Section: Substrate (Mm)mentioning
confidence: 99%
“…Based on these results, it was concluded that hyperammonemia of adult-type citrullinemia could result from the accumulation of free ammonia which was produced from thn catabolism of amino acids absorbed frcm the small intestine and surpassed the urea synthesis of defective urea cycle to flood into the blood. Furthermore, the rise of blood ammonia level at the night of the first fasting day suggested that the circadian rhythm of amino acid-carbohydrate metabolim might superimpcse on the process mentioned above, adult-type citrullinemia; hyperammonemia; diurnal fluctuation A 48-year-old man with adult-type citrullinemia has been described in our previous report (Yajima et al 1981). He showed repetitive episodes of encephalopathy and was diagnosed by quantitative estimation of amino acids and urea cycle enzymes in the liver.…”
mentioning
confidence: 92%